Managing projects : create your schedule, monitor your budget, meet your goals, - HArvard Business School (20 minute manager series, 2014)
You've been asked to manage a key project--or perhaps you've volunteered for an assignment that could advance your career. So how do you make sure the project succeeds? Managing Projects walks you quickly through the basics, including :Drawing up a realistic schedule and project plan. Monitoring key tasks and benchmarks. Communicating with stakeholders. Bringing the project to a close. Monitoring key tasks and benchmarks. Communicating with stakeholders. Bringing the project to a close. Don't have much time? Get up to speed fast on the most essential business skills with HBR's 20-Minute Manager series. Whether you need a crash course or a brief refresher, each book in the series is a concise, practical primer that will help you brush up on a key management topic. Advice you can quickly read and apply, for ambitious professionals and aspiring executives--from the most trusted source in business.